(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study investigates the complexities of help-seeking skills, academic achievement, personality traits, and barriers encountered during the process of seeking assistance. The research objectives include examining the correlation between help-seeking skills and academic achievement among undergraduate students majoring in English as a Foreign Language (EFL), exploring the association between help-seeking skills and personality characteristics, and identifying the barriers faced by students when seeking help. The study adopts a descriptive qualitative approach, involving three students in their 14th semester and two students in their 12th semester from the Department of English Literature as participants. Data collection methods include interviews, documentation of GPA scores, and Myers-Briggs Type Indicator (MBTI) assessments. The findings demonstrate that help-seeking skills significantly influence students’ GPA scores, personality traits shape individuals’ help-seeking behavior, and barriers to seeking help encompass stigma and embarrassment, negative experiences, and a preference for self-reliance.